Identification of Family Specific Fingerprints in β-Lactamase Families - Abhishikha Srivastava; Neelja Singhal; Manisha Goel; Jugsharan Singh Virdi; Manish Kumar (The Scientific World Journal)
Beta-lactamases are a superfamily of enzymes which degrade the β-lactam class of antibiotics. They are produced endogenously by the bacterial cells, which when exposed to the β-lactam class of antibiotics inactivate them by cleaving the β-lactam ring. Based on the presence or absence of metallic ligand, β-lactamases have been divided into two broad functional classes. β-Lactamases are a constitutively evolving and expanding superfamily of enzymes, which could be further subdivided on the basis of presence/absence of conserved motifs. In the present study we have used the MEME/MAST suit to identify the patterns/motifs which are specific to a particular family or subfamily of β-lactamases. The family specific patterns/motifs can be also useful in recognizing and assigning newly discovered β-lactamases to one or the other family or subfamily. Cross-validation showed that the proposed method is highly sensitive and specific. We have also designed a webserver, LactFP, for this purpose.